2018
DOI: 10.1111/evj.12837
|View full text |Cite
|
Sign up to set email alerts
|

Association of neutrophil morphology with bacterial isolates in equine tracheal wash samples

Abstract: Cytological evaluation of tracheal washes should include cytomorphological features of the neutrophil response. The presence of degenerate neutrophils, especially in young horses, indicates added value of culture and sensitivity for antimicrobial therapeutics. The absence of degenerate changes, in combination with clinical factors, can help support diagnosis of a nonseptic cause of airway neutrophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
2
7
1
Order By: Relevance
“…In the present study, ALP and LDH enzyme activities were determined in TW fluid of racehorses and mean ALP and LDH enzyme activities were found to be significantly higher in racehorses with both NS-LAD and S-LAD groups than healthy controls (P < 0.01). These results were in concordance with the previous studies performed in dogs [19], horses [13,23] and humans [5,8] mentioned above. In addition, LDH enzyme activity in the S-LAD group was determined to be higher (P < 0.01) than the NS-LAD group (Table 2).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, ALP and LDH enzyme activities were determined in TW fluid of racehorses and mean ALP and LDH enzyme activities were found to be significantly higher in racehorses with both NS-LAD and S-LAD groups than healthy controls (P < 0.01). These results were in concordance with the previous studies performed in dogs [19], horses [13,23] and humans [5,8] mentioned above. In addition, LDH enzyme activity in the S-LAD group was determined to be higher (P < 0.01) than the NS-LAD group (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…Local inflammatory cells such as alveolar macrophages and polymorphnuclear cells might had been a potential source of elevation in LDH concentration [5]. Especially in bacterial etiologies bacterial toxins causes degeneration and lysis of neutrophils and other cell types might have caused high LDH values as well [13]. In our study, based on cytology results were observed that increased levels of neutrophil (≥ 80%), degenerative cell changes and presence of intracellular bacteria in the septic inflammation group.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…More attention will need to be paid in future to morphology and perhaps typing of cells. The existence of neutrophil extracellular traps (NETosis) in horses with severe EA presents an additional method to determine response to treatment ( 67 ), and recently the presence of degenerate neutrophils has been shown to raise suspicion for bacterial infection ( 68 ). The question of macrophage morphology as an indicator of inflammation is also an area that will profit from further investigation ( 69 ).…”
Section: Recommended Minimum Database For Diagnosis Of Equine Asthma mentioning
confidence: 99%
“…This cross‐sectional study by Natasha Jocelyn and colleagues in the UK aimed to characterise the relevance of neutrophil morphology in tracheal wash (TW) samples in horses with respiratory disease .…”
Section: Tracheal Wash Cytologymentioning
confidence: 99%